2020
DOI: 10.1136/neurintsurg-2019-015506
|View full text |Cite
|
Sign up to set email alerts
|

How to WEB: a practical review of methodology for the use of the Woven EndoBridge

Abstract: wide-necked bifurcation aneurysms (wNBAs) make up 26-36% of all brain aneurysms. Treatments for wNBAs pose unique challenges due to the need to preserve major bifurcation vessels while achieving a durable occlusion of the aneurysm. intrasaccular flow disruption is an innovative technique for the treatment of wNBAs. The woven endoBridge (weB) device is the only United States Food and Drug Administration approved intrasaccular flow disruption device. in this review article we discuss various aspects of treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 24 publications
1
99
1
1
Order By: Relevance
“…Transverse size of the aneurysm is important, because the WEB device requires lateral compression to prevent device compaction. 14 It was found that sizing the device was based partially on aneurysm width, but ultimately on aneurysm volume, which achieved optimal device selection in the majority of cases. It may be appropriate to slightly oversize the WEB device in cases that the intent is to endoluminally remodel the aneurysm, as the radial force of the stent can be used to prevent herniation of the WEB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transverse size of the aneurysm is important, because the WEB device requires lateral compression to prevent device compaction. 14 It was found that sizing the device was based partially on aneurysm width, but ultimately on aneurysm volume, which achieved optimal device selection in the majority of cases. It may be appropriate to slightly oversize the WEB device in cases that the intent is to endoluminally remodel the aneurysm, as the radial force of the stent can be used to prevent herniation of the WEB.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its design, the WEB device should be deployed parallel to the axis of the aneurysm to achieve the greatest neck coverage. 14 The steep angulation at which nonbifurcation aneurysms arise from the parent vessel often increases the difficulty of achieving a stable orientation of the delivery microcatheter that is parallel to the aneurysm axis. Therefore, in all cases except one, the Via microcatheter required steam shaping to appropriately deploy the WEB device into the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 26–36% of intracranial aneurysms (IAs) are wide-neck bifurcation aneurysms (WNBAs), defined as aneurysms with neck diameters ≥4 mm and a dome-to-neck ratio of ≤2 mm [ 1 , 2 ]. Endovascular treatment of WNBAs is challenging because it requires embolization of the aneurysm while preserving the bifurcation vessels to achieve complete occlusion [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…610 Manufacturer recommendations and expert opinion recommend triaxial access for placement of the WEB device. 11 , 12…”
Section: Introductionmentioning
confidence: 99%